2013
DOI: 10.2310/jim.0b013e31827c2971
|View full text |Cite
|
Sign up to set email alerts
|

Serum Pentraxin 3 Levels are Associated with the Complexity and Severity of Coronary Artery Disease in Patients with Stable Angina Pectoris

Abstract: Pentraxin 3, a novel inflammatory marker, was more tightly associated with the complexity and severity of CAD than hs-CRP and was found to be an independent predictor for high SYNTAX score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
4
24
0
3
Order By: Relevance
“…Plasma PTX3 is more closely associated with the angiographic complexity and severity of CAD than is CRP [34]. Furthermore, we found that the prevalence of the no-reflow phenomenon was higher in the high-PTX3 group.…”
Section: Discussionmentioning
confidence: 55%
“…Plasma PTX3 is more closely associated with the angiographic complexity and severity of CAD than is CRP [34]. Furthermore, we found that the prevalence of the no-reflow phenomenon was higher in the high-PTX3 group.…”
Section: Discussionmentioning
confidence: 55%
“…9,27) Furthermore, plasma PTX3 is more closely associated with the angiographic complexity and severity of coronary artery disease than hs-CRP. 28) However, whether systemic PTX3 levels reflect plaque characteristics remains unclear. The present study therefore evaluated the relationship between systemic PTX3 levels and coronary plaque vulnerability assessed by The present study has a number of limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Pentraxin-related protein PTX-3 is one of the long pentraxins and, like CRP, is produced and released in the liver as an acute-phase response to proinflammatory cytokines, and also from within the unstable atherosclerotic plaque. 12,13 During the process of atherogenesis, PTX3 is found to be expressed in human vascular smooth muscle cells via atherogenic lipoproteins, 14 and is thought to upregulate tissue factor expression in human endothelial cells 15 and activated monocytes, 16 and to occur extensively in advanced atherosclerotic plaques. The present study showed that PBMC PTX-3 levels were significantly increased in patients with ACS compared with the controls.…”
Section: Discussionmentioning
confidence: 99%